Nepali Communist and Their Internalized Cultural Values - Adhikari, Kanshi Prasad (Academia Research Journal, 2023)
The communist political leadership in Nepal is the subject of this article, which focuses on their ideology and practices. Despite the fact that they identify as communists and support ideal political systems that feature equality, freedom, citizenry, the rule of the working class, and universal human rights, their internalized cultural values are centered on the hegemonic domination of one cultural group, gender, kinship, religion, area, and also serve the interests of power and wealth. The main features of communist political leadership are factionalism, opportunism, anarchy, individualism, petty bourgeoisie egoism, ultra leftism, double roles like right and leftist, reactionary and revisionist, as well as double roles like right and left. They declared themselves to be radical anarchist individualists who supported the monarchy in addition to adhering to Marxist, Leninist, and Maoist ideologies. The paper's foundation for this is scientific work in the areas of anthropology, sociology, political science, history, and other subjects by authors from Nepal and abroad. This study's major objective is to close the gap between communist leadership theory and practice in Nepal. Which of their internalized traditional cultural ideas have an impact on their leadership responsibilities? In order to analyze social scientists who are based on the communist leadership of Nepal and other nations, the paper uses empirical research with a primary focus on the study.